Real effects of sovereign bond market spillovers in the euro area - Niklas Gadatsch (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2015)
This paper develops a small open economy model to investigate the impact of rising sovereign bond market spreads on the real economy. One key element of the model is a "sovereign risk channel" through which tensions in the sovereign bond market tend to spill over into private credit markets. The model is estimated with Bayesian methods and data for "high-spread" countries in the euro area. It turns out that spread shocks during the Euro crisis had a negative effect on real GDP growth in these countries, up to 0.8 percentage points (PP) Portugal and Ireland, 0.3 PP in Italy and 0.2 PP in Spain.
Keywords: E32; E43; F41; 330; Small open economy; Business cycles; Sovereign risk premium; DSGE modeling